Astrocyte Modulation of Neurotoxic Injury - Aschner, Michael (Brain Pathol, 2006)
Astrocytes produce trophic factors, regulate neurotransmitter and ion concentrations, and remove toxins and debris from the extracellular space of the CNS, maintaining an extracellular milieu that is optimally suited for neuronal function. Consequently, astrocytic functional impairments, as well as physiological reactions of astrocytes to injury have the potential to induce and/or exacerbate neuronal dysfunction. This mini‐review showcases contemporary evidence provoking reformulation of concepts of the inter‐dependence between astrocytes and neurons and advances several mechanisms used by astrocytes in potentiating or nullifying the final pathway of neuropathologic injury. Though clearly possessing an array of protective systems and upregulating a large number of protective molecules in response to xenobiotic exposure, recent evidence also invokes astrocytes in secondary amplification of cell injury in multiple neurodegenerative disorders.